La foi catholique et les dispositifs numériques : le cas de la diaspora catholique vietnamienne - Anh Ngoc HOANG (Tic & Société)
Catholic Faith and Digital Media. The case of the Vietnamese Diaspora – This study aims to provide initial insights into the relationship between the Catholic faith and digital media through the particular case of the Vietnamese Catholic diaspora. Drawing on an "epistemology of complexity", this investigation attempts to articulate new possibilities offered by sociotechnical objects with actual usages and practices by Internet users. Through a semiotic analysis of two websites and a sociological survey by questionnaire and interviews, the study will show the way this diasporic population uses digital devices to imagine new practices of their Catholic faith in a situation of geographic dispersion. It highlights a particular Catholicism of overseas Vietnamese characterized by a transnational dimension and an integration of online and offline faith practices. This novel reality poses challenges as well as opening up new perspectives for the Roman Catholic Church in the digital age, now confronted with tensions between long-standing “solid” traditions and contemporary “liquid” connections.